Spectrum of Clinical Manifestations in Turkish Patients with Williams-Beuren Syndrome: A Monocentric Study - Semra Gürsoy; Filiz Hazan; Cüneyt Zihni; Sezer Acar; Murat Muhtar Yılmazer; Timur Meşe; Behzat Özkan (Galenos Yayinevi, 2021)
Aim:Williams-Beuren syndrome, which is characterized by dysmorphic facial features, cardiovascular findings, intellectual disability, endocrine abnormalities and a typical cognitive profile, is caused by a microdeletion in the 7q11.23 region. In this study, we aimed to evaluate the dysmorphic and clinical manifestations of patients with Williams-Beuren syndrome.Materials and Methods:We retrospectively collected data from 27 Turkish patients who had clinically and genetically confirmed Williams- Beuren syndrome. Their multisystemic manifestations, demographic data and dysmorphic facial features were recorded.Results:All patients had the characteristic facial phenotype. The most frequent dysmorphic facial features were periorbital fullness, short nose, broad nasal tip and wide mouth. Aortic stenosis (59.2%) and pulmonary stenosis (37%) were the most common cardiac findings. Short stature (25.9%), idiopathic central precocious puberty (7.4%), hypothyroidism (congenital, non-congenital or subclinical) (40.7%) and hypercalcemia (3.7%) were the major endocrine manifestations in the patients. Genitourinary abnormalities were detected in 6 patients. All patients had some degree of intellectual disability; most of the patients (62.9%) had mild intellectual disability. Additionally, behavioral problems were frequently detected and the most common abnormality was overfriendliness (77.7%). Renal abnormalities (double collecting system, bladder diverticula and renal calculi) were also detected.Conclusion:Dysmorphic facial features, which have a crucial role in the diagnosis of Williams-Beuren syndrome, should be assessed in suspected patients with supravalvular aortic stenosis and concomitant intellectual disability in order to make an early diagnosis. It should be kept in mind that endocrine abnormalities, musculoskeletal, neurologic and psychiatric manifestations are also common in patients with Williams-Beuren syndrome, necessitating a multidisciplinary approach.